Clinical role of CYP1B1 gene polymorphism in prediction of postoperative chemotherapy efficacy in NSCLC based on individualized health model - Liu, Bo; Zhang, Shaofeng; Liu, Chunyan; Han, Xia (Open life sciences, 2023)
Non-small cell lung cancer (NSCLC) is one of the most common cancers worldwide, and chemotherapy is one of its main treatment methods. However, there are significant differences in patients’ reactions to chemotherapy, leading to unsatisfactory treatment outcomes. Therefore, identifying relevant factors that affect the efficacy of chemotherapy can help doctors better develop personalized treatment plans, improve the treatment effectiveness, and quality of life of patients. This article aims to understand the specific clinical role of CYP1B1 gene in NSCLC. Therefore, based on the individualized health model of CYP1B1 gene polymorphism, this article analyzes the prediction of postoperative chemotherapy efficacy for NSCLC. Through a study on the control variables of postoperative recovery of stage III NSCLC in a hospital, according to the findings of this study, 14 of the 32 patients in the EGFR mutation-positive group relapsed. In the EGFR-negative group, 13 of the 36 patients relapsed. It can be considered that CYP1B1 gene polymorphism has a good curative effect in postoperative chemotherapy of NSCLC, and it can effectively control the recurrence rate of cancer.